Oral Presentations Abstracts: SHARING WHILST CARING: SOLIDARITY AND PUBLIC TRUST IN A DATA-DRIVEN HEALTHCARE SYSTEM - HORN, Ruth; KERASIDOU, Angeliki (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 In the UK, the solidaristic character of the NHS makes it one of the most trusted public institutions. In recent years, the introduction of data-driven technologies in healthcare has opened up the space for collaborations with private digital companies seeking access to patient data. However, these collaborations appear to challenge the public’s trust in the healthcare system. In this paper we explore how the opening of the healthcare sector to private digital companies challenges the existing social contract and the NHS’s solidaristic character, and impacts on public trust. We start by critically discussing different examples of partnerships between the NHS and private companies that collect and use data. We then analyse the relationship between trust and solidarity, and investigate how this relationship changes in the context of digital companies entering the healthcare system. Finally, we show ways for the NHS to maintain public trust by putting in place a solidarity grounded partnership model with companies seeking to access patient data. Such a model would need to serve collective interests through, for example, securing preferential access to goods and services, providing health benefits, and monitoring data access. A solidarity grounded partnership model will help establish a social contract or licence that responds to the public’s expectations and to principles of a solidaristic healthcare system.